The achievement Of University Technology MARA Cawangan Sarawak client’s charter from the industry perspective: A case study In Kuching, Sarawak / Mariam Rahmat … [et.al.] - Rahmat, Mariam; Lee, Elinda Ai Lim; Narawi, Susana (2004)
Many parties have debated the issue of unemployment and quality of graduates because they are worried about the 'skills gap or the 'mismatch between the types and quality of graduates produced by the universities and their employability skills. UiTMCS as a learning institution has established work norms and quality standards for its outputs or services to its stakeholders. These norms and standards have been transformed into a written commitment known as the Client's Charter. One of its commitments is to supply manpower that fulfills the needs of industries in the country. The purpose of this study is to determine how far UiTMCS has fulfilled its commitment expounded in the client's charter from the industry perspective. This study examines the performance of UiTMCS graduates in two dimensions, that is, knowledge and expertise, and attitude and conduct. It will also determine the level of acceptance of the employers towards them. Snowballing and judgmental techniques were employed to identify the subjects, that is, UiTMCS recent graduates who have working experiences of two years and below in the government, statutory bodies and the private sector in Kuching, Sarawak. The data were collected through a set of self-administered questionnaire and were answered by their employers. The findings indicate that the overall performance of UiTMCS graduates was favorable in both the dimensions of knowledge and expertise, and attitude and conduct.